Análisis de las exportaciones de cacao tipo CCN51 en el Ecuador y su contribución en el producto interno bruto durante el periodo 2014-2018 - Lema Martínez, Ericka Jahaira (2021)
The export of cocoa type CCN51 plays an important role in the Ecuadorian economy. Knowing these figures is of vital relevance, since it is evident that their growth and / or decrease significantly influence non-oil exports in the trade balance, directly affecting income in GDP. In this sense, this research is proposed with the objective of analyzing the behavior of CCN51 cocoa exports and how it contributed to GDP during the 2014-2018 period. To carry out this research, theoretical support was referenced and statistical information was collected, all of which can be used to determine the evolution and / or change of the research variables and their relationship through a correlation analysis. The applied methodology was of a mixed approach of deductive, analytical-statistical type based on reliable theoretical, documentary, bibliographic and correlational information with the application of interviews to professionals in the area……